Attachment‐based family therapy in the age of telehealth and COVID‐19. (22nd March 2021) - Levy, Suzanne; Mason, Syreeta; Russon, Jody; Diamond, Guy
Abstract: The COVID‐19 pandemic has transformed so many aspects of our lives. For psychotherapists, telehealth is likely a permanent part of the future mental health landscape. For family therapists using a manualized treatment, this brings unique challenges and creative opportunities. In this article, we describe the adaptation of attachment‐based family therapy (ABFT) in the context of telehealth and COVID‐19. ABFT is an empirically supported treatment model designed for adolescents and young adults struggling with depression, anxiety, trauma, and suicide. ABFT is a semi‐structured, process‐oriented, and trauma‐informed family therapy model which presents its own unique challenges and benefits in telehealth environments. We present our adaptations based on years of telehealth clinical experience and address how this model supports the impact of COVID‐19 on families.